Current dietary intake of the Japanese population in reference to the planetary health diet-preliminary assessment - Nomura, Marika; Yamaguchi, Miwa; Inada, Yuji; Nishi, Nobuo (Frontiers in Nutrition, 2023)
Introduction We sought to assess the Japanese diet by examining the current dietary intake in Japan using the global reference diet from the EAT-Lancet Commission (Planetary Health Diet; PHD), from the perspective of protein intake in different age groups. Methods Average dietary intake by food group in the Japan National Health and Nutrition Survey 2019 (NHNS 2019) was converted to the PHD food groups, and the diet gap (DG) (%) of the global reference of the PHD was calculated by age group. Results Although the DG of the intake was excessive compared with the global reference of the PHD in most food groups in all age groups (7.1–416%), the intake exceeded the upper limit of the range only for red meat (640%). Red meat had the highest DG among subjects in their 40s, although the DG decreased with increasing age. Protein intake was within the possible range and did not greatly exceed the recommended dietary intake in the Japanese standard. Discussion The current Japanese diet contains an excessive intake of red meat in terms of the global reference of the PHD. This trend is similar to that previously reported in various western regions and countries. However, the Japanese diet does not significantly exceed the recommended protein intake for Japanese people, suggesting that the PHD is an environmentally friendly and healthy choice for younger and older age groups in an aging Japanese society. Policy makers need to develop sustainable and healthy food-based dietary guidelines in addition to providing food and nutrition education and developing a food environment that encourages sustainable and healthy choices to support dietary change.